2019
DOI: 10.1016/j.mnl.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Changing Culture to Drive Nurse Engagement and Superior Patient Experience

Abstract: Brandon "Kit" Bredimus was the recipient of AONL's 2018 Pamela Austin Thompson Early Careerist Award. He helped to develop and implement the program detailed below, which improved nurse engagement and patient experience scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It has been suggested that a patient's experience is influenced by the engagement of caregivers and all hospital employees who play a role in that patient's care (19,20). Further, physicians contend that provider and staff engagement lead to improved quality and patient experience outcomes (21).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a patient's experience is influenced by the engagement of caregivers and all hospital employees who play a role in that patient's care (19,20). Further, physicians contend that provider and staff engagement lead to improved quality and patient experience outcomes (21).…”
Section: Introductionmentioning
confidence: 99%
“…2 Indeed, evidence shows that soft skills such as relationship building, effective communication, enthusiasm, emotional intelligence, and interpersonal skills can improve nurse engagement, patient experience, and overall nursing leadership effectiveness. 2,3 What do these skills look like in actual practice as a leader? How can you learn and use these skills in practice to improve your effectiveness as a leader?…”
mentioning
confidence: 99%